KARAKTERISTIK BIO-FISIK HABITAT PANTAI PENELURAN TERHADAP TINGKAT KEBERHASILAN PENETASAN TELUR PENYU HIJAU (Chelonia mydas) DI PULAU PENYU PESISIR SELATAN PROVINSI SUMATERA BARAT - Puji Cintami Tambun; Hesti Wahyuningsih; Yoes Soemaryono (AQUACOASTMARINE, 2018)
Green Turtle (Chelonia mydas) is an endangered marine reptile because of its high economic value. The main threats to the Green Turtle population from human activities, such as coastal and marine pollution, destruction of spawning habitats, destruction of feeding areas, migration disruption, illegal sea turtle fishing and turtle egg collection. This research took place in May - July 2017 at Turtle Island Pesisir Selatan West Sumatera Province. The measurements obtained were 1.53 km of coastline, coastal width ranging from 15.5 - 24.5 m, coastal slope ranging from 23.8 – 29.2˚, semi diurnal tidal type, nest distances from the highest tides ranging from 8 to 9.5 m, the lowest nest distance from 13.5 - 14.5 m, the nest distance of the plant ranges from 2 to 10 m, the nest substrate consists of sand, clay, and dust which is dominated by sand, measured nest size during the study ranges from L 62 - 65 cm, P 100 - 105 cm, D 36 - 38 cm, d 38 - 39 cm, t 23-25 cm, measured temperature range 27 ° C - 30 ° C, temperature measured 27 ˚C - 29˚C, pH value nest 7, measured rainfall 400 mm/month, nest number found 8 nests, consisting of 4 Green Turtle nest (Chelonia mydas) and 4 Hawksbill turtle nests (Eretmochelys imbricata). The highest hatching percentage was 95.23% and the lowest was 24.21%.Keywords: Green Turtle (Chelonia mydas), characteristic, bio-physical, hatching percentage, Turtle Island